The Role of Vitamin D in Inflammatory Bowel Disease Pathogenesis and Management - Randy Adiwinata; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2017)
Vitamin D is widely recognized in maintaining bone metabolism and health. However, recent studies indicated that vitamin D also play important role in regulating immune system. Patients with inflammatory bowel disease (IBD) is commonly found to be vitamin D deficiency; whether it served as risk factor of IBD or as the consequence of disease activity are still debatable. Growing evidences showed that supplementation of vitamin D for IBD patients to achieve normal or optimal serum level may suppress the inflammatory process, reduce disease severity, maintaining remission status, and improving quality of life.